Pengaruh Pembiayaan Murabahah, Mudharabah, Musyarakah Terhadap Profitabilitas (Studi Kasus Pada Perusahaan Perbankan Syariah Di Indonesia Periode 2020 - 2022) - Nada Berliana; Murniati (CV. ITTC INDONESIA, 2024)
This research aims to test and conduct an analysis of the influence of murabahah, mudharabah and musyarakah financing on the profitability of Islamic banks in Indonesia in 2020-2022. This research uses quantitative research methods using data in the form of numbers. Secondary data is in the form of annual reports found on the websites of each sharia bank in Indonesia and on the financial services authority (OJK) website. The sampling technique used purposive sampling, 11 Islamic banks were sampled in this study over a 3 year period. This research was assisted by SPSS computers using descriptive tests, classical assumption tests and multiple linear regression tests. The results of this research show that murabahah financing has a significant effect on profitability, mudharabah financing has no effect on profitability and musyarakah financing has no effect on profitability.